Eloquence in Raphael drawings - Whistler, C; Thomas, B (IRSA Publishing House, 2016)
In this paper, which presents aspects of our research for an exhibition to be held at the Ashmolean Museum and the Albertina in 2017, we examine Raphael’s drawings in relation to the concept of eloquence. Two types of eloquence emerge in this analysis: one permeating the court culture in which Raphael worked based on rhetoric and poetic theories of imitation, and the other type of material eloquence arising from Raphael’s handling of his drawing materials, and his pursuit through them of viable formal inventions. Although Raphael is more usually associated in discussions of art theory with a type of eclectic imitation predicated on the ‘Idea’, close attention to the artist’s drawings reveals a process of revision and adaptation of motifs that calls into question this ‘hylomorphic model’ of creativity, and places him closer to Pietro Bembo’s view that creativity derives from ‘long labour, practice and exercise’.